Effects of sleep pattern, duration, and quality on premenstrual syndrome and primary dysmenorrhea in korean high school girls - Daye Jeong; Heakyong Lee; Jaehee Kim (BMC, 2023)
Abstract Background Sleep deprivation is known to be a risk factor for premenstrual syndrome and primary dysmenorrhea in adults. However, it has rarely been investigated in adolescents. The aim of this study was to investigate whether sleep pattern, duration, and quality independently affect premenstrual syndrome and primary dysmenorrhea in adolescent girls. An additional purpose was to investigate the sleep status in Korean adolescent girls during the COVID-19 pandemic. Methods A cross-sectional survey study was conducted in 519 high school girls aged 15 to 18 years in Gyeonggido, South Korea, in 2021 during the COVID-19 lockdown. Menstrual pain intensity and menstrual symptoms were assessed using the visual analogue scale (VAS) and Cox menstrual symptom scale (CMSS), respectively. Premenstrual syndrome was assessed by the premenstrual symptoms screening tool (PSST). Sleep was assessed by the Pittsburgh Sleep Quality Index (PSQI). The known risk factors of dysmenorrhea, including menstrual and lifestyle characteristics and stress, were assessed as covariates. Results During the pandemic, approximately 68% of girls slept 7 h or less, while about 60% reported poor sleep quality. Additionally, 64% of participants had a bedtime later after 1AM, and 34% woke up later after 8AM. Late bedtime significantly affected VAS (P = 0.05), CMSS severity and frequency (both P < 0.01), and PSST symptom (P < 0.01). Waking up late affected CMSS severity (P < 0.05), PSST symptom (P = 0.05), and PSST function (P < 0.05). However, the significance of these effects disappeared after controlling for covariates. Sleeping less than 5 h affected CMSS frequency (P < 0.05) and PSST symptoms (P < 0.001). After controlling for covariates, the significance of the effect on PSST symptom remained (P < 0.05). General sleep quality and PSQI components, including subjective sleep quality, sleep latency, sleep disturbance, use of sleeping medication, and daytime dysfunction, significantly affected CMSS frequency and severity and PSST symptom after controlling for covariates (P < 0.05, P < 0.01, or P < 0.001). The multiple regression analysis revealed that among sleep characteristics, sleep quality was the most important risk factor of premenstrual syndrome and dysmenorrhea. Conclusion Our study result heightens the importance of healthy sleep hygiene, especially sleep quality in the management of premenstrual syndrome and dysmenorrhea in adolescent girls.